Activated carbon and biochar from pineapple waste biomass for the removal of methylene blue - Mahmud, Khoirun Nisa; Wen, Tan Hui; Zakaria, Zainul Akmar (Environmental and Toxicology Management, 2021)
Dye pollution in water system is of concern due to its carcinogenicity and its effect on aesthetic feature. One pollutant of interest is methylene blue (MB), which is a cationic dye widely used in industries. In this study, pyrolysis process was used to convert pineapple waste biomass (PWB) into useful adsorbents such as biochar (BC) and activated carbon (AC) to remove MB in water. BC was produced from pyrolysis of PWB (340 °C, 3 hours) whereas AC was prepared from pyrolysis of PWB (500 °C, 1 hour) impregnated with zinc chloride (ZnCl2). Prior to use, AC-PWB and BC-PWB were characterized for surface area, functional groups and surface morphology. Removal of MB was investigated by varying different parameters i.e. initial MB concentration and contact time, adsorbent dosage and temperature. Results obtained showed that AC-PWB has higher adsorption capacity than BC-PWB. The adsorption capacity and adsorption rate increased with increasing initial concentration of MB, adsorbent dosage and temperature until reached equilibrium condition. As a conclusion, PWB can be used as a useful raw material to produce cheap and environmentally friendly adsorbent to remove dye from solution.